Kerangka Kerja Asesmen Akademik, Komunikasi, Serta Pembelajaran Sosial dan Emosional (PSE) dan Perkembangan Bagi Anak - Fitria Putri; Nadila Azura Febriati; Zirul Habibi; Opi Andriani (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Effective learning for children with Autism Spectrum Disorder (ASD) requires appropriate assessment. ASD children have three main disorders, including communication. An important assessment stage is carried out with the aim of finding information regarding the level of communication skills, needs and weaknesses of children with ASD. Therefore, appropriate assessment tools are needed to find out information about the communication aspects of children with ASD. The aim of this research is to develop a tool to assess the communication skills of children with ASD. Communication and language barriers are encountered from a very young age in children with autism spectrum disorder (ASD). ASD children are children with developmental disorders characterized by difficulties in aspects of interaction and communication as well as repetitive and rigid patterns of behavior and interests according to the Diagnostic Statistical Manual (DSM) V criteria (Senouci, 2021).